Performance and Energy Efficiency Analysis of a Rooftop Photovoltaic System in an Office Building Using SolisCloud - Roal, Mario; Julianto, Heri; Ferdyanto (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2026)
upport the energy transition and improve electricity consumption efficiency. This study aims to evaluate the performance of a rooftop PV system and analyze the efficiency of electricity consumption at the DISPERINDAG ESDM Office Building of West Kalimantan Province. The research was conducted as a case study using a quantitative and evaluative approach, based on operational data of the PV system obtained from the SolisCloud application during 2024, as well as electricity consumption data before and after the installation of the PV system. System performance was evaluated using the Performance Ratio (PR) and Yield Factor (Yf) parameters in accordance with the IEC 61724-1:2017 standard. The results show that the PV system generated a total electrical energy of 30,719 kWh, with an average PR value of 70.72% and a Yf of 3.36 kWh/kWp. Electricity consumption from the PLN grid decreased from 81,259 kWh in 2023 to 61,684 kWh in 2024, resulting in an electricity consumption efficiency of 24%.